THE CORRELATION BETWEEN BREAST CARE WITH THE INCIDANCE OF BREASTMILK DAMS AT NS BABY SPA AND MOM CARE CLINIC MEDAN JOHOR DISTRICT MEDAN CITY IN 2019 - Munthe, Juliana; Sinuhaji, Lidya Natalia; Sinaga, Martaulina; Ginting, Siska; Ginting, Astaria Br; Egatamara, Ucha (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Breast milk dams are of milk due narrowing of the lactic ducts or by the glands not being enptied completely or due to abnormalities in the nipples. Breast milk dam is the occurrence of swelling in the breast due to increased venous and lymph flow which causes milk dams and pain accompanied by an increase in body temperature (Winkjosastro, 2016). The purpose of this study was to determine in the relationship between breast care and the incidence of ASI dams in the Ns Baby Spa And Mom Care Clinic Medan Johor District Medan City in 2019. This type of research is an observational analytic case control study approach. The population was all breastfeeding mothers who experienced breastfeeding dam events in the 2019 Ns Baby Spa And Mom Care Clinic , totaling 80 people. The number of samples used was 31 people obtained using simple random sampling technique. Data collection using questionnaires and checklist sheets to monitor the management of breast care. Data analysis techniques and checklist sheets to monitor the management of breast care. Data analysis techniques using the chi square test. The results obtained are p value (0,000) which means there is a relationship between breast care and the incidence of breast milk dams at the Ns Baby Spa And Mom Care Clinic in Medan Johor District Medan City in 2019.